Improving Students’ Achievement in Reading Descriptive Text through Reciprocal Teaching Strategy - Rohdearni Wati Sipayung (BIRCU, 2018)
This paper describes how to improve students’ achievement in reading descriptive text through reciprocal teaching strategy. The sample of this paper are 21 Students of VIII-1 Grade in Senior High School of PTPN IV Bah Jambi. The pre- test data were distributed before the treatment of Reciprocal Teaching Strategy and the post-test data were taken after the treatment of teaching-learning reading descriptive text by using Reciprocal Teaching Strategy. The finding shows before the treatment of Reciprocal Reading Strategy, the basic knowledge of students at grade VIII SMP Swasta PTPN IV Bah Jambi was low since the mean of pre-test data was 25,95 and after the treatment, the students’ achievement in reading descriptive text was good where the mean of post-test data was 69,76 so that the mean difference before and after the treatment was 43,81